GMMA-based vaccine candidates against invasive nontyphoidal salmonellosis elicit bactericidal antibodies against a panel of epidemiologically relevant Salmonellae - De Simone, Daniele; Pinto, Marika; Aruta, Maria Grazia; Benincasa, Marta; Carducci, Martina; Di Benedetto, Roberta; Citiulo, Francesco; Iturriza, Miren; Mylona, Elli; Baker, Stephen; Pizza, Mariagrazia; Giannelli, Carlo; et al. (Frontiers in Immunology, 2025)
Systemic disease caused by nontyphoidal Salmonella (NTS) represents a major cause of death and morbidity, especially in young children in sub-Saharan Africa. No licensed vaccine is yet available, and an increase in antimicrobial resistance makes the development of a vaccine a global health priority. We are developing a bivalent formulation of Salmonella Typhimurium and Salmonella Enteritidis generalized modules for membrane antigens (GMMA)–based vaccine (iNTS-GMMA) and a trivalent formulation (iNTS-TCV) in which iNTS-GMMA is combined with the WHO-prequalified TYPHIBEV (Biological E, India) vaccine to prevent typhoid fever in addition to invasive NTS (iNTS) disease. Here, we measured the ability of antibodies induced by iNTS-GMMA and iNTS-TCV formulations in mice and rabbits to kill a broad panel of Salmonella in vitro in a complement-mediated fashion. These organisms include those causing invasive disease in Africa and Southeast Asia, global representatives causing gastroenteritis and other S. enterica serovars in addition to S. Typhimurium and S. Enteritidis. We characterized the O-antigen of the panel of isolates and demonstrated the sera functionality in both animal species against all isolates, providing evidence of the potential broad coverage of both GMMA-based formulations, which are currently undergoing testing in Phase I/II clinical trials.